2012
DOI: 10.1021/am201619u
|View full text |Cite
|
Sign up to set email alerts
|

Silica Nanoparticles and Frameworks from Rice Husk Biomass

Abstract: Biogenic silica nanoparticles (25-30 nm in diameter) were synthesized from rice husks. The characterizations revealed that the silica nanoparticles were composed of smaller primary particles (ca. 4.2 nm in diameter), and their clustering led to a porous structure with a surface area of 164 m(2)/g. Under the controlled melting catalyzed by K(+), such silica nanoparticle clusters can gradually fuse to form semicrystalline porous silica frameworks with tunable pore size and structural integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
106
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(120 citation statements)
references
References 43 publications
11
106
0
3
Order By: Relevance
“…In the step of converting RHs to nano-SiO 2 , simply burning RHs in air will produce bulk SiO 2 , and it is necessary to first perform HCl leaching7 and then only heat at moderate temperatures to avoid the fusion of the SiO 2 product (Fig. 2a–c) while removing the organic matter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the step of converting RHs to nano-SiO 2 , simply burning RHs in air will produce bulk SiO 2 , and it is necessary to first perform HCl leaching7 and then only heat at moderate temperatures to avoid the fusion of the SiO 2 product (Fig. 2a–c) while removing the organic matter.…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, silica obtained in this way is relatively pure and accounts for as much as ~20% of the dry weight of the RHs6. Moreover, the silica within the RHs naturally exists in the form of nanoparticles7. As a living plant, rice absorbs silica in the form of silicic acid from soil, and the silica accumulates around cellulose micro-compartments8910, as illustrated in Supplementary Fig.…”
mentioning
confidence: 97%
“…Hydrochloric acid was proven as an effective acid used in pre-treatment before calcination to remove most of the metallic impurities and producing high purity silica. Therefore, many researchers succeeded in obtaining high purity silica from RH, for instance Mishra et al [13], Della et al [14], Swatsitang et al [15], Wang et al [16] and Jung et. al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there is an increasing demand for eco-friendly disposal and utilization of RHA. Many studies indicated that it was a promising low-cost candidate for preparation of silica nanoparticles [1820]. Nano-sized silica can be used to form nanofluids with special interest because of its high specific surface area, excellent stability, high mechanical resistance, and possibility of reuse [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…The commercially available silica nanoparticles are typically prepared by using a silica precursor as silicon source, such as silicon alkoxide (typically silicon tetraethoxysilane). However, the synthesis of silica precursors is usually energy intensive and associated with high cost, eco-hazardous, and unsustainability issues [18]. …”
Section: Introductionmentioning
confidence: 99%